EMPIRICAL COST STUDY AND ECONOMIC THEORY. - Bornemann, Alfred (The Accounting Review, 1945)
Abstract The article presents information on empirical cost study and economical theory. In recent years there has been a growing interest in measuring what is known as the cost function. While several economists have directed their attention to the actual calculations, a greater number are likely to become interested in some of the many problems which have been disclosed. The larger problems relate to certain significant implications of the conclusions arrived at in these studies. An analysis of the issues involved will perhaps contribute to their clarification. The empirical investigation of cost functions involves the measurement of the relationship between cost and output. It is thought that such studies may be significant because "cost behavior has a crucial role in determining the most profitable adjustment of the individual enterprise to its economic environment." In considering these efforts to calculate the cost function, it is necessary to recall some essential elements of economic theory. In economic theory a distinction is made between the short run and the long run.